Implementation of Virtual Synchronous Machine Control Using EV Battery’s SOC for Single-Stage Converter During Battery Charging - Momoh, Kabir; Zulkifli, Shamsul Aizam; Korba, Petr; Segundo Sevilla, Felix Rafael; Velazquez-Ibañez, Alfredo; Afandi, Arif Nur (2025)
The increasing adoption of electric vehicles (EVs) has necessitated the development of advanced controllers during battery charging. Those controllers are vital for maintaining current stability at the point of common coupling (PCC) during battery charging and the power flow response to the battery in order to maintain the battery’s voltage. This paper introduces an improved virtual synchronous machine (i-VSM) control using the battery’s state-of-charge (SOC) voltage as the virtual flux model for the motor’s concept. The i-VSM model adapted the SOC condition, the grid phase angle for power demand, and the reactive power flow between the PCC and the EV. A three-phase rectifier converter behaving as a fast-charging station (FCS) module was integrated into the i-VSM model to reflect the EV battery’s SOC condition. The i-VSM model was verified in MATLAB software in order to demonstrate grid stability quality, especially on grid-side current total harmonic distortion (THD) and in maintaining the voltage at the PCC. In the simulation, the i-VSM model was tested with an FCS rated at 150 kW. The virtual inertia maintains the frequency control at PCC and reduces the power oscillation when the load at the PCC was increased from 50 kW to 150 kW. The grid-side current THD was at 3.67%, which was the allowable value at the PCC. If this proposed controller is implemented in future power stations, the FCSs will not affect the grid’s condition, and furthermore the controller will increase grid stability and is able to maintain the voltage of different-rated EVs.